Tubes For X-Ray Structure Analysis - Elmurotova Dilnoza Baxtiyorovna; Ismatova Lobar Numonovna; Xaitov Farxod Nasriddinovich; Odilova Nilufar Jurayevna (Genius Journals, 2022)
In this work considered the basis of the method of measuring X-ray diffraction analysis and the properties of soft X-ray radiation. Shown the practical problems of the Wulf-Bragg relation and studied the properties and operation of the X-ray diffraction tube.
Keywords: X-ray diffraction analysis; tube; target; K-lines